The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1128/iai.01049-16
|View full text |Cite
|
Sign up to set email alerts
|

Human Three-Dimensional Endometrial Epithelial Cell Model To Study Host Interactions with Vaginal Bacteria and Neisseria gonorrhoeae

Abstract: Colonization of the endometrium by pathogenic bacteria ascending from the lower female reproductive tract (FRT) is associated with many gynecologic and obstetric health complications. To study these host-microbe interactions in vitro, we developed a human three-dimensional (3-D) endometrial epithelial cell (EEC) model using the HEC-1A cell line and the rotating wall vessel (RWV) bioreactor technology. Our model, composed of 3-D EEC aggregates, recapitulates several functional/structural characteristics of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 68 publications
2
43
0
Order By: Relevance
“…These discrepancies could be due to a lack of cell polarization or stratification and a lack of bacterial growth in the monolayer system. The results from a three-dimensional tissue model of G. vaginalis infection are in agreement with this study in that no significant increases in the secretion of TNF-␣, IL-6, or IL-8 were detected (60). These data partly reflect in vivo cytokine profiles in BV-positive women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These discrepancies could be due to a lack of cell polarization or stratification and a lack of bacterial growth in the monolayer system. The results from a three-dimensional tissue model of G. vaginalis infection are in agreement with this study in that no significant increases in the secretion of TNF-␣, IL-6, or IL-8 were detected (60). These data partly reflect in vivo cytokine profiles in BV-positive women.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, cervicovaginal colonization by G. vaginalis in pregnant mice resulted in increased levels of IL-6 in cervicovaginal fluid as well as increased IL-1␤, IL-8, and IL-10 gene expression in cervical tissue (59). In a human three-dimensional endometrial epithelial cell model, however, G. vaginalis did not elicit any significant changes in the secretion of IL-6, IL-8, or tumor necrosis factor alpha (TNF-␣) compared to a mock-infected control (60). Similarly, when G. vaginalis was added to organotypic cultures of human vaginal epithelium containing dendritic cells, there was no stimulation of H␤D-2, IL-8, or IL-1 (␣ or ␤) expression, albeit bacteria were heat inactivated prior to inoculation of tissues (61).…”
mentioning
confidence: 96%
“…Similar to the VMB, the endometrial microbiota may be able to modulate inflammation. In vitro co-cultures of endometrial epithelial cells with pathogenic bacteria ( Neisseria gonorrhoeae ) induced proinflammatory mediators ( Christodoulides et al, 2000 ), whereas other bacteria typically found in the reproductive microbiotas ( Lactobacillus crispatus , Gardnerella vaginalis ) did not ( Łaniewski et al, 2017 ). This suggests that the endometrial microbiota may be able to modulate endometrial inflammation in the host.…”
Section: The Female Genital Tractmentioning
confidence: 99%
“…It was the first technology used to develop 3-D models for infection studies with bacterial (Salmonella) and viral (rhinovirus) pathogens (11,51). A range of RWV-derived 3-D models have been developed using cell lines, stem cells, and/or primary cells, including small and large intestine (11,80,141,143,145,146,152,(168)(169)(170)(171)(172)(173)(174)(175)(176)(177), lung (144,147,(178)(179)(180)(181)(182), liver (148,153,174,183,184), bladder (8,(185)(186)(187), reproductive tissue (149)(150)(151)(188)(189)(190), heart (191)(192)(193), prostate (142,186,194), pancreas (195,<...>…”
Section: Modeling the Microenvironment: 3-d Models For Infectious Dismentioning
confidence: 99%